TINDAK PIDANA PERDAGANGAN ORANG: ANALISIS UNDANG-UNDANG NO. 21 TAHUN 2007 - Alfitra (Jurnal Hukum Islam, 2009)
Although the laws have regulated trafficking, even been set in the Criminal Code, but not all of those can easily overcome the problem. Poverty and employment problems are considered as the causes of trafficking. Children and women, as the majority of trafficking victims, rarely report the crime they have experinced. So, the laws and regulations of trafficking need to get more attention and widely socialized.